Pengetahuan Pasien Tentang Diet Cairan dan Nutrisi pada Pasien Gagal Ginjal Kronik (GGK) Di Ruang Hemodialisa RSUD Kabupaten Indramayu Tahun 2017 - Hikmawati, Kitri (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Chronic renal failure is a clinical condition of kidney damage which can cause the body fails to maintain metabolism and fluid and electrolyte balance, which causes uremia and fluid build up. Knowledge of diet fluids management and nutrition in renal failure patient is important to know and for those who are determined to reduce the risk of kidney disorders. The purpose of this research is to know the description of Patient’s Knowledge about Fluid and Nutrition Diet in Chronical Renal Failure (GGK) in hemodialysis room of RSUD Indramayu 2017